Italian nurses' experiences of the COVID-19 pandemic through social media: A longitudinal mixed methods study of Internet posts. (October 2022) - Rossettini, Giacomo; Peressutti, Verena; Visintini, Erica; Fontanini, Roberta; Caruzzo, Davide; Longhini, Jessica; Palese, Alvisa
Objective: To examine the experience of Italian nurses posted on social media and discover changes, if any, over the waves. Methods: A mixed methods study reported according to the Good Reporting of a Mixed Methods Study criteria. All narratives (texts, letters and interviews) posted by Italian nurses from February 2020 to May 2020 (first wave) and from October 2020 to May 2021 (second/third wave) on the five most famous Italian professional social media platforms. The data were analysed qualitatively (first wave) and then quantitatively (second/third wave). Results: A total of 380 narratives (202, 626 words, 2510 quotes) were posted in the first wave, and 161 (68, 388 words, 835 quotes) in the second/third wave. In the first wave, the following five themes emerged: (a) 'sharing what is happening within myself' (891; 35.5%); (b) 'experiencing unprecedented working conditions' (749; 29.8%); (c) 'failing to rehabilitate the image of nurses in society' (376; 15%); (d) 'experiencing a deep change' (253; 10.1%) and (e) 'do not abandon us' (241; 9.6%). The same themes and subthemes also emerged in the second/third wave with some significant differences, indicating changes in the lived experience of nurses. Moreover, in the second/third wave, a new theme emerged: 'experiencing the mixed emotions towards jabs'. Conclusions: By analysing their posts, Italian nurses continue to face challenges during the COVID-19 pandemic, with changes in their lived experiences across the waves. Governments, nursing associations and health care organizations should consider these changes to design policies to prevent the further loss of nurses.